Preparation method of catalyst for treating synthetic rubber tail gas

CN119368171APending Publication Date: 2025-01-28SHANGHAI DONGHUA ENVIRONMENT ENG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310903091.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The precious metal catalysts used in the prior art for treating synthetic rubber exhaust gases have problems such as high cost, low utilization rate and easy poisoning failure, and the catalysts have poor stability at high temperatures, making it difficult to meet the needs of industrial applications.

Method used

Multi -layer composite carriers and sodium borohydride are used as boron sources. Steps such as water heat treatment and ultrasonic cleaning are prepared to prepare low load -load -load precious metal catalysts to improve the activity and stability of the catalyst.

Benefits of technology

The high temperature stability, low temperature activity of catalysts, good low temperature activity, larger surface area, high decentralization of activity components, strong antiex and anti -sintering capacity, improved the efficiency and economy of tail gas treatment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a catalyst for treating synthetic rubber tail gas, which comprises the following steps of: performing hydrothermal pretreatment on two carrier coatings in a reducing atmosphere, sequentially coating the two carrier coatings on the surface of honeycomb metal, and roasting a coated honeycomb metal carrier containing a composite coating by taking sodium borohydride as a boron source to obtain the catalyst for treating synthetic rubber tail gas. And finally, preparing a platinum group metal-containing compound, a surfactant, a solvent and an auxiliary agent into a solution with a certain concentration, impregnating the honeycomb metal carrier containing the composite coating with the solution, and drying and roasting the honeycomb metal carrier containing the composite coating to obtain the noble metal catalyst with the modified honeycomb metal containing the composite coating as the carrier. The synthesized catalyst can effectively remove harmful components such as normal hexane, butadiene and the like in synthetic rubber tail gas, has good hydrothermal stability, low initiation temperature, wide applicable temperature range, high conversion efficiency, good strength, stable catalyst activity, low noble metal loading capacity and higher utilization rate, and has obvious environmental protection benefits and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for preparing a catalyst for treating synthetic rubber tail gas. Background Art

[0002] The synthetic rubber device generates rubber waste gas during the production process, with an emission volume of tens of thousands of Nm 3 / h, the concentration of non-methane total hydrocarbons is several thousand mg / Nm 3 , the main pollutants in the exhaust gas are hexane, butadiene, etc., which have a great impact on the surrounding environment. In view of the exhaust emission characteristics of the synthetic rubber industry, the selective catalytic oxidation method is the most economical and effective treatment method for treating substances such as n-hexane and butadiene in the exhaust gas. In this process, the main factor affecting the exhaust gas treatment effect is the catalyst. In terms of efficiency and energy consumption, the catalyst performance plays a decisive role. Due to the high average concentration of n-hexane in the exhaust gas of synthetic rubber devices in actual industry, the heat release is large, the catalytic combustion temperature is high, and the fluctuation range of n-hexane concentration is large. A large amount of water vapor is generated during the combustion reaction. Therefore, the catalyst is required to have high high-temperature stability, good low-temperature activity, large specific surface area, high dispersion of active components, and strong anti-poisoning and anti-sintering capabilities.

[0003] The catalysts currently used to treat the tail gas of synthetic rubber devices are mainly precious metal catalysts with platinum (Pt) and palladium (Pd) as the main active ingredients. They have excellent catalytic performance and high thermal stability, and are the mainstream catalysts used to treat the tail gas of synthetic rubber devices. However, the precious metal active components have a high loading and large size, so that the only active components that really participate in the catalytic reaction are those exposed on the outer surface of the catalyst. The utilization rate of the precious metal active components is low, and the reaction is not thorough. In addition, precious metal catalysts have the problems of high price and easy poisoning and failure. Therefore, how to prepare efficient, stable and low-cost precious metal catalysts and apply them to the treatment of synthetic rubber device tail gas is an urgent problem to be solved.

[0004] Chinese patent CN116173944A uses a reductant to thermally reduce a palladium-platinum precursor to achieve a slow synthesis method, which uses the nano-size effect to achieve uniform dispersion of the two metals at the atomic level, thereby improving the catalyst activity. However, noble metal atoms, clusters, and nanoparticles are prone to thermal sintering, which causes the catalyst to become inactivated due to Ostwald ripening during long-term operation.

[0005] Chinese patent CN114984942B prepared a precious metal catalyst with rare earth metal oxide (cerium) and metal oxide (aluminum) as carriers, and used a reducing atmosphere to generate more oxygen vacancies on the composite oxide carrier, thereby improving the catalyst activity. However, the interface between the precious metal and the carrier is single, and only the precious metal on the catalyst surface effectively participates in the catalytic process, resulting in a large amount of precious metal being wasted. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, according to an embodiment of the present invention, it is hoped to provide a method for preparing a catalyst for treating synthetic rubber exhaust gas, which provides a solution to the aforementioned problem. The catalyst prepared by the method has good hydrothermal stability, low ignition temperature, wide applicable temperature range, high conversion efficiency, good strength, stable operation of the exhaust gas treatment device and catalyst activity, low precious metal loading, higher utilization rate, and obvious environmental and economic benefits when treating synthetic rubber exhaust gas.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows.

[0008] In a first aspect, the present invention provides a method for preparing a catalyst for treating synthetic rubber tail gas, the preparation method comprising the following steps:

[0009] (1) Carrier pretreatment

[0010] In a mixed flowing atmosphere of hydrogen and argon, the mixed solution containing zirconium, cerium and aluminum is heated to 50-100° C. and subjected to hydrothermal treatment for 5-10 hours to obtain coating slurry I;

[0011] In a flowing atmosphere of hydrogen and argon, the mixed solution containing cerium, titanium and silicon is heated to 50-100° C. and subjected to hydrothermal treatment for 5-10 hours to obtain coating slurry II;

[0012] The honeycomb metal is ultrasonically cleaned multiple times.

[0013] (2) Composite carrier preparation

[0014] The coating slurries I and II obtained in step (1) are sequentially coated on the surface of the honeycomb metal, and after drying and calcination, a honeycomb metal carrier containing a composite coating is obtained. The honeycomb metal carrier containing a composite coating and sodium borohydride are sequentially placed in the rear zone and the front zone of a tubular furnace, the temperature of the front zone of the tubular furnace is increased to 500° C., and the modified composite coating honeycomb metal carrier is treated for 30 minutes under a flowing atmosphere of argon.

[0015] (3) Active metal loading

[0016] A compound containing at least two of the platinum group metals iridium (Ir), rhodium (Rh), palladium (Pd), and platinum (Pt), a surfactant, a solvent, and an additive are prepared into a solution of a certain concentration, and the solution is repeatedly impregnated on the modified composite coating honeycomb metal carrier obtained in step (2). Finally, the catalyst for treating synthetic rubber tail gas is obtained by drying and calcining.

[0017] Preferably, the mixed solution containing zirconium, cerium and aluminum in step (1) is prepared by dissolving metal salts in a solvent, wherein zirconium is selected from zirconium sulfate tetrahydrate, cerium is selected from cerium nitrate hexahydrate, and aluminum is selected from pseudo-boehmite. The mixed solution containing cerium, titanium and silicon is prepared by dissolving metal salts in a solvent, wherein cerium is selected from cerium nitrate hexahydrate, titanium is selected from tetrabutyl titanate, and silicon is selected from ethyl orthosilicate. The solvents are all selected from at least one of methanol, hexane, ethanol, ethylene glycol, glycerol, acetone and dimethylformamide. In the present invention, different carrier components are coated in layers, which can increase the interface between the active component and the carrier, allowing faster oxygen vacancy recovery to achieve better dispersibility. When the carrier component is selected from the above components, the catalyst effect is optimal. This is because the preferred carrier component can induce a strong metal-carrier effect, encapsulate and capture precious metal clusters, reduce the particle size of the precious metal, and produce more oxygen vacancies, which is conducive to improving the catalytic activity.

[0018] Preferably, the composition of the coating slurry I in step (1) includes: 0.1-8 parts by weight of a zirconium source (zirconium sulfate tetrahydrate), 0.1-6 parts by weight of a cerium source (cerium nitrate hexahydrate), 10-50 parts by weight of an aluminum source (pseudo-boehmite) and 30-70 parts by weight of a solvent. For example, the zirconium source can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts. The cerium source can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts. The aluminum source can be 10 parts, 20 parts, 30 parts, 40 parts, 50 parts. The solvent may be 30 parts, 40 parts, 50 parts, 60 parts, or 70 parts.

[0019] The composition of coating slurry II includes: 0.1-6 parts by weight of cerium source (cerium nitrate hexahydrate), 1-10 parts by weight of titanium source (tetrabutyl titanate), 10-50 parts by weight of silicon source (ethyl orthosilicate) and 30-60 parts by weight of solvent. For example, the cerium source can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts. The titanium source can be 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts. The silicon source can be 10 parts, 20 parts, 30 parts, 40 parts, 50 parts. The solvent can be 30 parts, 40 parts, 50 parts, 60 parts. Too little carrier component will lead to insufficient dispersion of active components during the reaction, which is easy to sinter or poison. Too much support component will lead to lower catalytic oxidation activity.

[0020] Preferably, the volume ratio of hydrogen to argon in step (1) is 1 / 1-1 / 10. For example, it can be 1 / 1, 1 / 2, 1 / 3, 1 / 4, 1 / 5, 1 / 6, 1 / 7, 1 / 8, 1 / 9, 1 / 10. Hydrogen can be adsorbed and overflowed on the surface of the carrier, causing changes in the properties of the carrier, and then causing changes in the interaction interface between the active metal and the carrier. Too much or too little hydrogen in the reducing atmosphere will affect the local structure of the active center constructed by the reduction, change the valence and structure of the carrier, affect the interaction between the active component and the carrier, and cause a decrease in the activity of the catalyst.

[0021] Preferably, in step (2), the heating rate of the tubular furnace is 3-5°C / min.

[0022] Preferably, in step (3), the compound containing platinum group metals iridium (Ir), rhodium (Rh), palladium (Pd), platinum (Pt) is selected from any one of oxides, hydroxides, nitrates, chlorates or colloids of the corresponding active components. The surfactant is selected from at least one of calcium carbonate, aluminum sol, nitric acid, and diethylene glycol. The solvent is selected from any one of water, acetone, toluene, hexane, methanol, ethanol, or dimethylformamide. The auxiliary agent is selected from at least one of p-aminophenoxy zirconate, ethylenediamine N-ethoxy zirconate, and 3-aminopropyltriethoxysilane.

[0023] Preferably, in step (3), the amount of the compound precursor containing platinum group metals added is 0.1-1 parts by weight, the amount of the solvent added is 1-50 parts by weight, the amount of the surfactant added is 3-30 parts by weight, and the amount of the auxiliary agent added is 0-0.3 parts by weight.

[0024] In a second aspect, the present invention provides a catalyst, which is prepared by the aforementioned preparation method.

[0025] In the third aspect, the present invention provides an application of the aforementioned catalyst, specifically an application in the treatment of synthetic rubber tail gas. In actual industry, the average concentration of n-hexane in the tail gas of synthetic rubber devices is relatively high, the heat release is large, the catalytic combustion temperature is relatively high, and the fluctuation range of n-hexane concentration is large. A large amount of water vapor is generated during the combustion reaction process, so the catalyst is required to be very high. When the catalyst prepared by the preparation method of the present invention is used to treat synthetic rubber tail gas, the catalytic temperature is 250 to 580°C, and the water concentration in the exhaust gas is 0 to 30%. It has the characteristics of high high temperature stability, good low temperature activity, large specific surface area, high dispersion of active components, and strong anti-poisoning and anti-sintering capabilities.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] A multilayer composite carrier was prepared to form a unique surface structure, which is conducive to adjusting the affinity between the surface adsorbate and the substrate, thereby producing high catalytic activity, which can effectively improve the activity, selectivity, and stability of the catalyst for the reaction and reduce the cost of the catalyst. The oxygen vacancies on the composite carrier are further increased by reducing atmosphere, which is conducive to the activation of oxygen and the formation of surface hydroxyl radicals, further improving the catalytic activity.

[0028] By using sodium borohydride as the boron source, a low-loading and structure-controllable supported noble metal catalyst was prepared, allowing faster oxygen vacancy recovery for better dispersion, thereby providing more available mobile oxygen, while greatly preventing the migration and agglomeration of noble metal nanoparticles and improving the catalyst's ability to resist poisoning. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments. The present invention illustrates the detailed process equipment and process flow of the present invention through these embodiments, but the present invention is not limited to these detailed process equipment and process flow, that is, it does not mean that the present invention must rely on these detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, the equivalent replacement of each raw material of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0030] Example 1

[0031] (1) 5.5 g of zirconium sulfate tetrahydrate, 3.8 g of cerium nitrate hexahydrate, and 10.5 g of pseudo-boehmite were added to 50.0 g of ethanol, and a hydrogen / argon mixed gas (1 / 5) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 50° C. and hydrothermally treated for 8 h while stirring to obtain a coating slurry I;

[0032] (2) 1.2 g of cerium nitrate hexahydrate, 5.0 g of tetrabutyl titanate, and 15.8 g of ethyl orthosilicate were added to 60.0 g of ethanol, and a hydrogen / argon mixed gas (1 / 2) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 50° C. and subjected to hydrothermal treatment for 8 h while being stirred to obtain coating slurry II;

[0033] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0034] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0035] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0036] (6) dissolving 100 mg of potassium tetrachloropalladate and 69.6 mg of potassium chloroplatinate in a mixed solution of 10 ml of water and 30 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0037] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 1.

[0038] Example 2

[0039] (1) 8.0 g of zirconium sulfate tetrahydrate, 0.1 g of cerium nitrate hexahydrate, and 50.0 g of pseudo-boehmite were added to 70.0 g of hexane, and a hydrogen / argon mixed gas (1 / 10) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 60° C. and subjected to hydrothermal treatment for 8 h while being stirred to obtain coating slurry I;

[0040] (2) 6.0 g of cerium nitrate hexahydrate, 10.0 g of tetrabutyl titanate, and 50.0 g of ethyl orthosilicate were added to 45.0 g of hexane, and a hydrogen / argon mixed gas (1 / 5) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 60° C. and subjected to hydrothermal treatment for 8 h while being stirred to obtain coating slurry II;

[0041] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0042] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0043] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0044] (6) dissolving 100 mg of potassium tetrachloropalladate and 69.6 mg of potassium chloroplatinate in a mixed solution of 10 ml of water and 30 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0045] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 2.

[0046] Example 3

[0047] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry I;

[0048] (2) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0049] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0050] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0051] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0052] (6) dissolving 100 mg of potassium tetrachloropalladate and 69.6 mg of potassium chloroplatinate in a mixed solution of 10 ml of water and 30 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0053] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 3.

[0054] Example 4

[0055] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry I;

[0056] (2) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0057] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0058] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0059] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0060] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0061] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 4.

[0062] Comparative Example 1

[0063] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium sulfate pentahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry I;

[0064] (2) 5.2 g of cerium sulfate pentahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0065] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0066] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0067] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0068] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0069] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 5.

[0070] Comparative Example 2

[0071] (1) 1.2 g of zirconium nitrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain coating slurry I;

[0072] (2) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0073] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0074] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0075] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0076] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0077] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 6.

[0078] Comparative Example 3

[0079] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (2 / 1) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain a coating slurry I;

[0080] (2) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 1) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0081] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0082] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0083] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0084] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0085] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 7.

[0086] Comparative Example 4

[0087] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry I;

[0088] (2) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0089] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0090] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0091] (5) immersing the honeycomb substrate in step (4) in coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and treating at 500° C. for 30 minutes under a flowing atmosphere of argon to obtain a composite coated honeycomb metal substrate;

[0092] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0093] (7) Using nitrogen as the protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 8.

[0094] Comparative Example 5

[0095] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain a coating slurry;

[0096] (2) A 50×50×50 mm cube honeycomb metal was ultrasonically cleaned multiple times;

[0097] (3) immersing the cleaned honeycomb metal in the coating slurry, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120°C for 8 hours and calcining at 650°C for 3 hours;

[0098] (4) placing the honeycomb substrate in step (3) and 5.0 g of sodium borohydride in the rear zone and the front zone of the tubular furnace in turn, raising the temperature of the front zone of the tubular furnace to 500° C., and treating for 30 min under a flowing atmosphere of argon to obtain a modified composite coated honeycomb metal substrate;

[0099] (5) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (4);

[0100] (6) Using nitrogen as a protective gas flow, the material obtained in step (5) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 9.

[0101] Comparative Example 6

[0102] (1) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain a coating slurry;

[0103] (2) A 50×50×50 mm cube honeycomb metal was ultrasonically cleaned multiple times;

[0104] (3) immersing the cleaned honeycomb metal in the coating slurry, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120°C for 8 hours and calcining at 650°C for 3 hours;

[0105] (4) placing the honeycomb substrate in step (3) and 5.0 g of sodium borohydride in the rear zone and the front zone of the tubular furnace in turn, raising the temperature of the front zone of the tubular furnace to 500° C., and treating for 30 min under a flowing atmosphere of argon to obtain a modified composite coated honeycomb metal substrate;

[0106] (5) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (4);

[0107] (6) Using nitrogen as a protective gas flow, the material obtained in step (5) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 10.

[0108] Comparative Example 7

[0109] (1) 4.6 g of cerium nitrate hexahydrate and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain coating slurry I;

[0110] (2) 5.2 g of cerium nitrate hexahydrate and 32.0 g of tetraethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain coating slurry II;

[0111] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0112] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0113] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0114] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0115] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 11.

[0116] Comparative Example 8

[0117] (1) 1.2 g of zirconium sulfate tetrahydrate and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was introduced into the bottom for bubbling at a flow rate of 5 ml / min. The mixture was heated to 100° C. for hydrothermal treatment for 5 h while stirring to obtain coating slurry I;

[0118] (2) 5.2 g of cerium nitrate hexahydrate and 3.2 g of tetrabutyl titanate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain coating slurry II;

[0119] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0120] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0121] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0122] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0123] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 12.

[0124] Comparative Example 9

[0125] (1) 0.1 g of zirconium sulfate tetrahydrate, 8.0 g of cerium nitrate hexahydrate, and 7.5 g of pseudo-boehmite were added to 80.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry I;

[0126] (2) 5.2 g of cerium nitrate hexahydrate, 3.2 g of tetrabutyl titanate, and 32.0 g of ethyl orthosilicate were added to 30.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and subjected to hydrothermal treatment for 5 h while being stirred to obtain coating slurry II;

[0127] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0128] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0129] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0130] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0131] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 13.

[0132] Comparative Example 10

[0133] (1) 1.2 g of zirconium sulfate tetrahydrate, 4.6 g of cerium nitrate hexahydrate, and 21.5 g of pseudo-boehmite were added to 45.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 7) was bubbled into the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry I;

[0134] (2) 8.2 g of cerium nitrate hexahydrate, 0.5 g of tetrabutyl titanate, and 52.0 g of ethyl orthosilicate were added to 25.0 g of propylene glycol, and a hydrogen / argon mixed gas (1 / 3) was bubbled at the bottom at a flow rate of 5 ml / min. The mixture was heated to 100° C. and hydrothermally treated for 5 h while stirring to obtain coating slurry II;

[0135] (3) ultrasonically clean a 50×50×50 mm cube honeycomb metal multiple times;

[0136] (4) immersing the cleaned honeycomb metal in coating slurry I, using an air knife to blow off the extra slurry, and then drying the coated honeycomb support at 120° C. for 8 hours and calcining at 650° C. for 3 hours;

[0137] (5) immersing the honeycomb substrate in step (4) in the coating slurry II, using an air knife to blow off the extra slurry, and then drying the obtained composite coated honeycomb metal substrate at 120° C. for 8 hours, and then placing it and 5.0 g of sodium borohydride in the rear zone and front zone of a tubular furnace in sequence, raising the temperature of the front zone of the tubular furnace to 500° C., and treating it in a flowing atmosphere of argon for 30 minutes to obtain a modified composite coated honeycomb metal substrate;

[0138] (6) dissolving 180 mg of potassium tetrachloropalladate and 169.6 mg of potassium chloroplatinate in a mixed solution of 20 ml of water and 50 ml of diethylene glycol to prepare a palladium-platinum mixture precursor solution, and repeatedly impregnating the solution on the modified composite coating honeycomb metal support obtained in step (5);

[0139] (7) Using nitrogen as a protective gas flow, the material obtained in step (6) was dried at 120° C. for 8 hours, and then calcined at 600° C. for 5 hours to obtain catalyst 14.

[0140] The catalysts provided in the above Examples 1-4 and Comparative Examples 1-10 were subjected to performance tests, and the performance test method was as follows:

[0141] The catalytic activity of the samples was carried out in a stainless steel reactor equipped with a heating furnace at normal pressure. Before each experiment, a 50×50×50mm cube honeycomb catalyst sample was pretreated with flowing nitrogen (30mL / min) at 120°C for 2h. Then, a gas mixture containing the reaction gas and dry air was introduced into the reactor for reaction.

[0142] The flow of reaction gas and air is controlled by a mass flow meter. The composition of reaction gas is 1000ppm of n-hexane, 500ppm of butadiene, and 30% of water content (mass fraction). The rest is air. The test temperature is 250℃ and 580℃, and the air velocity is 20000h-1. The pre-mixed reaction gas can directly enter the reaction tube or pass through a homemade bubbling device (the water vapor content in the mixed reaction gas can be changed by controlling the gas flow rate and the bubbler temperature) and then enter the reaction tube. The catalytic performance and stability of the catalyst under dry and water vapor conditions can be measured respectively. The reaction product is analyzed online by gas chromatograph. The chromatographic column is composed of two capillary columns of Porapak Q and 5A molecular sieve in parallel, and FID is used as the detector. The conversion rate of each substance in the reaction gas is calculated by the correction factor carbon normalization method.

[0143] The specific results are shown in Table 1 (sample reaction performance table):

[0144] Table 1

[0145]

[0146] The following conclusions can be drawn from the results data measured under the two reaction temperature conditions in Table 1:

[0147] Comparison of Examples 1 and 4 shows that the catalyst prepared by the preparation method of the present invention can greatly reduce the precious metal loading while having little effect on the catalytic activity. This difference is almost negligible when the reaction temperature reaches 550°C.

[0148] In Comparative Examples 1 and 2, the source of the raw materials of the coating slurry has an impact on the catalyst performance, but this impact is more obvious when the reaction temperature is 250°C. When the temperature rises to 550°C, the source of the components has little impact on the overall effect of the catalyst.

[0149] In Comparative Example 3, when the ratio of hydrogen to argon exceeds the scope of this patent, the conversion rate will be greatly reduced. This is because the valence and structure of the carrier have changed, affecting the interaction between the active metal and the carrier, resulting in a decrease in the activity of the catalyst.

[0150] In Comparative Example 4, sodium borohydride was not used to pretreat the carrier, and the conversion rates of n-hexane and butadiene in the reaction gas also decreased. This is because the release of oxygen vacancies was affected.

[0151] It can be seen from the results of Comparative Examples 5-8 that when the carrier coating layer coated on the honeycomb metal carrier in the catalyst lacks a certain layer or one or more components are missing in a certain layer, the conversion rate will be greatly reduced.

[0152] It can be seen from the results of Examples 1-4 and Comparative Examples 9 and 10 that the carrier coating in the present invention has a better reaction effect under a certain ratio, and when the ratio exceeds a certain range, the effect of the catalyst will decrease.

[0153] Based on the above findings, Examples 1 and 4 of the present invention have high catalytic activity and stable performance in a high humidity and heat environment with a reaction temperature of 250-550°C and a water content of 30%. According to the actual industrial synthetic rubber tail gas situation and emission requirements, appropriate raw materials, proportions, and preparation steps can be selected according to the catalyst preparation method disclosed in the present invention to prepare a preferred catalyst with the best catalytic effect and economic effect.

Claims

1. A method for preparing a catalyst for treating synthetic rubber tail gas, characterized in that: The following steps are involved: (1) Carrier pretreatment In a mixed flowing atmosphere of hydrogen and argon, the mixed solution containing zirconium, cerium and aluminum is heated to 50-100° C. and subjected to hydrothermal treatment for 5-10 hours to obtain coating slurry I; In a flowing atmosphere of hydrogen and argon, the mixed solution containing cerium, titanium and silicon is heated to 50-100° C. and subjected to hydrothermal treatment for 5-10 hours to obtain coating slurry II; The honeycomb metal is ultrasonically cleaned; (2) Composite carrier preparation The coating slurries I and II obtained in step (1) are sequentially coated on the surface of the honeycomb metal, and after drying and calcining, a honeycomb metal carrier containing a composite coating is obtained; The honeycomb metal carrier containing the composite coating and sodium borohydride are placed in the rear zone and the front zone of the tube furnace in sequence, the temperature of the front zone of the tube furnace is increased to 500°C, and the modified composite coating honeycomb metal carrier is obtained by treating the carrier in an argon flowing atmosphere for 30 minutes; (3) Active metal loading A compound containing at least two of the platinum group metals iridium Ir, rhodium Rh, palladium Pd, and platinum Pt, a surfactant, a solvent, and an additive are prepared into a solution of a certain concentration, and the solution is repeatedly impregnated on the modified composite coated honeycomb metal carrier obtained in step (2). Finally, the solution is dried and calcined to obtain a catalyst for treating synthetic rubber tail gas.

2. The method for preparing a catalyst for treating synthetic rubber tail gas according to claim 1, characterized in that: In step (1), a mixed solution containing zirconium, cerium and aluminum is prepared by dissolving metal salts in a solvent, wherein zirconium is selected from zirconium sulfate tetrahydrate, cerium is selected from cerium nitrate hexahydrate, aluminum is selected from pseudo-boehmite, and the solvent is selected from at least one of methanol, hexane, ethanol, ethylene glycol, glycerol, acetone and dimethylformamide; a mixed solution containing cerium, titanium and silicon is prepared by dissolving metal salts in a solvent, wherein cerium is selected from cerium nitrate hexahydrate, titanium is selected from tetrabutyl titanate, silicon is selected from tetraethyl orthosilicate, and the solvent is selected from at least one of methanol, hexane, ethanol, ethylene glycol, glycerol, acetone and dimethylformamide.

3. The method for preparing a catalyst for treating synthetic rubber tail gas according to claim 2, characterized in that: In step (1), the composition of coating slurry I includes: 0.1-8 parts by weight of zirconium sulfate tetrahydrate, 0.1-6 parts by weight of cerium nitrate hexahydrate, 10-50 parts by weight of pseudo-boehmite and 30-70 parts by weight of solvent; the composition of coating slurry II includes: 0.1-6 parts by weight of cerium nitrate hexahydrate, 1-10 parts by weight of tetrabutyl titanate, 10-50 parts by weight of ethyl orthosilicate and 30-60 parts by weight of solvent.

4. The method for preparing a catalyst for treating synthetic rubber tail gas according to claim 1, characterized in that: In step (1), the volume ratio of hydrogen to argon is 1 / 1-1 / 10.

5. The method for preparing a catalyst for treating synthetic rubber tail gas according to claim 1, characterized in that: In step (2), the heating rate of the tubular furnace is 3-5°C / min.

6. The method for preparing a catalyst for treating synthetic rubber tail gas according to claim 1, characterized in that: In step (3), the compound containing platinum group metals iridium Ir, rhodium Rh, palladium Pd, and platinum Pt is selected from any one of oxides, hydroxides, nitrates, chlorates, or colloids of platinum group metals; the surfactant is selected from at least one of calcium carbonate, aluminum sol, nitric acid, and diethylene glycol; the solvent is selected from any one of water, acetone, toluene, hexane, methanol, ethanol, or dimethylformamide; the auxiliary agent is selected from at least one of p-aminophenoxy zirconate, ethylenediamine N-ethoxy zirconate, and 3-aminopropyltriethoxysilane; in parts by weight, the amount of the compound precursor containing the platinum group metal added is 0.1-1 parts, the amount of the solvent added is 1-50 parts, the amount of the surfactant added is 3-30 parts, and the amount of the auxiliary agent added is 0-0.3 parts.

7. A catalyst for treating synthetic rubber tail gas prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the catalyst according to claim 7 in treating synthetic rubber tail gas.

9. The use according to claim 8, characterized in that: The catalytic temperature is 250-580°C, and the water concentration in the synthetic rubber waste gas is 0-30%.

Citation Information

Patent Citations

  • A catalyst for VOC catalytic combustion, its preparation method and application

    CN114984942B

  • Preparation method and application of palladium-platinum diatomic VOC oxidation catalyst

    CN116173944A